Randomized Clinical Trial on the Use of PHYSTA Freeze-Dried Water Extract of Eurycoma longifolia for the Improvement of Quality of Life and Sexual Well-Being in Men. (1st November 2012) - Ismail, Shaiful Bahari; Wan Mohammad, Wan Mohd Zahiruddin; George, Annie; Nik Hussain, Nik Hazlina; Musthapa Kamal, Zatul Mufiza; Liske, Eckehard
Abstract : Eurycoma longifolia is reputed as an aphrodisiac and remedy for decreased male libido. A randomized, double-blind, placebo controlled, parallel group study was carried out to investigate the clinical evidence of E. longifolia in men. The 12-week study in 109 men between 30 and 55 years of age consisted of either treatment of 300 mg of water extract of E. longifolia (Physta) or placebo. Primary endpoints were the Quality of Life investigated by SF-36 questionnaire and Sexual Well-Being investigated by International Index of Erectile Function (IIEF) and Sexual Health Questionnaires (SHQ); Seminal Fluid Analysis (SFA), fat mass and safety profiles. Repeated measures ANOVA analysis was used to compare changes in the endpoints. The E. longifolia (EL) group significantly improved in the domain Physical Functioning of SF-36, from baseline to week 12 compared to placebo (P = 0.006 ) and in between group at week 12 (P = 0.028 ). The EL group showed higher scores in the overall Erectile Function domain in IIEF (P < 0.001 ), sexual libido (14% by week 12), SFA- with sperm motility at 44.4%, and semen volume at 18.2% at the end of treatment. Subjects with BMI ≥ 25 kg/m 2 significantly improved in fat mass lost (P = 0.008 ). All safety parameters were comparable to placebo.